Keamanan krim anti jerawat berbasis kitosan cangkang kerang bulu : Safety in anti-acne cream based on chitosan from antique ark shells - Ukhradiya Magharaniq Safira Purwanto; Dara Anggun Vachyra; Dimas Andrianto (Jurnal Pengolahan Hasil Perikanan Indonesia, 2023)
Chitosan is a chitin derivative, which is known to have antimicrobial properties. These properties make chitosan have a potential as a cosmetics ingredient. This study aimed to determine the safety of anti-acne cream with the addition of chitosan from shells of antique ark shells (Anadara antiquata Linn.) from heavy metal and microbial contamination. Heavy metal content was tested with Atomic Absorption Spectrophotometry (AAS). Microbial contamination of the cream base and 5% chitosan cream was determined by measuring the total plate count (TPC) and yeast mold number (YMN) using the pour cup method. The levels of lead and mercury in shells met the standards with values ​​of 1.78 mg/kg and <0.004 mg/kg, respectively. The TPC values ​​for cream base and 5% cream also met the standards with successive values ​​of 8.3x102 cfu/mL and 7.2x104 cfu/mL, while the YMN values ​​did not meet the standards with consecutive values ​​of 2.2x104 cfu/mL and 1.4x104 cfu/mL. Cream with the addition of 5% chitosan showed lower TPC and YMN values ​​compared to cream base (control). Cream preparations with the addition of chitosan do not meet BPOM Indonesia's safety standards for YMN values.